The use of intraradicular retainers after endodontic treatment (Research, Society and Development, 2023)
Objective: Search the literature on the use of intraradicular retainers after endodontic treatment, comparing the factors that influence the resistance between fiberglass posts and cast metal posts. Methodology: This is a bibliographical investigation of a qualitative nature, through an integrative literature review. This scientific method provides a more comprehensive understanding of a particular topic or phenomenon. To construct the guiding question, the PICO (Population, Intervention, Control and Results) strategy was used, conducted according to the following elaboration stages: choice of theme, formulation of the guiding question, literature search, data collection, selection and critical analysis of studies, discussion of results and presentation of the review. Results: the fiberglass post showed better results in most push-out and union tests, in terms of elastic modulus these retainers demonstrated more similarity to that of dentin. In contrast, there are still studies stating that the cast metal post is the most suitable for clinical use due to stress distribution tests. Conclusion: The fiberglass post presented more advantages when compared to the metallic one, due to its elastic modulus similar to that of dentin, more favorable aesthetics, greater tensile strength and lower chances of fracture. Some factors, such as the scarcity of more current articles presenting the advantages of metal retainers, allowed a limited comparison, which may or may not influence the results.